BRCA2 gene mutation in cancer. Issue 45 (11th November 2022) - Xie, Chunbao; Luo, Jiangrong; He, Yangjun; Jiang, Lingxi; Zhong, Ling; Shi, Yi
Abstract : Breast cancer susceptibility gene 2 (BRCA2) is the main gene associated with hereditary breast cancers. However, a mutation in BRCA2 has also been found in other tumors, such as ovarian, pancreatic, thyroid, gastric, laryngeal, and prostate cancers. In this review, we discuss the biological functions of BRCA2 and the role of BRCA2 mutations in tumor progression and therapy.